3(6x+2)=6

Simple and best practice solution for 3(6x+2)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6x+2)=6 equation:



3(6x+2)=6
We move all terms to the left:
3(6x+2)-(6)=0
We multiply parentheses
18x+6-6=0
We add all the numbers together, and all the variables
18x=0
x=0/18
x=0

See similar equations:

| (X+17)=(5x+1) | | -129=8(c-6)+7 | | 5y-9y=25 | | 2x-3(2x+1)=4 | | (3x+1)=121 | | 7(-7x+9)=-378 | | 2/15m+1/5=4/5 | | 12+3x=2(x+1) | | (X+29)+(4x+1)=180 | | -6(6+6x)=-468 | | 3x=22+5x | | (3x)+(x+10)=90 | | 5(-6x+10)=80 | | 3/5x-2=26 | | (3x)=(x+10) | | -7x-10=-94+7x | | 12m-7=65 | | (6x-7)=(5.5x-3) | | 5n+30=180 | | 12+3x=(x+1) | | n/3+11=4.7 | | 7(9v-2)=-15 | | 4(-3x-4)=8 | | 5x+2+4x=29 | | 24-2n=18 | | x-7=-5x-31 | | (6x-7)=(11x-6) | | x+5=7x-13 | | b-9=3b=24 | | 2^2x-18×2^x=40 | | -1-6x=3x-82 | | 3x+63=33-13x |

Equations solver categories